2016
DOI: 10.1016/j.physbeh.2016.08.015
|View full text |Cite
|
Sign up to set email alerts
|

The Spanish version of the Three Factor Eating Questionnaire-R21 for children and adolescents (TFEQ-R21C): Psychometric analysis and relationships with body composition and fitness variables

Abstract: According to the psychometric analysis of the questionnaire, the TFEQ-R21C is a valid and useful tool to assess eating behaviors in Spanish child population. Further research is necessary to understand the links between eating behaviors and other health-related behaviors such as physical activity time or cardiovascular fitness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
50
3
1

Year Published

2017
2017
2025
2025

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(71 citation statements)
references
References 36 publications
16
50
3
1
Order By: Relevance
“…Similarly, a study of Spanish youth demonstrated that overweight participants scored higher on external eating, which involves a decreased sensibility to internal signals of hunger and satiety, compared to normal weight children [23]. Other studies, in contrast, have found a negative relationship, with lower uncontrolled eating scores in youth with higher BMI [7]. In the current study, uncontrolled eating or emotional eating was also positively correlated with energy leftover at dinner.…”
Section: Discussionsupporting
confidence: 60%
“…Similarly, a study of Spanish youth demonstrated that overweight participants scored higher on external eating, which involves a decreased sensibility to internal signals of hunger and satiety, compared to normal weight children [23]. Other studies, in contrast, have found a negative relationship, with lower uncontrolled eating scores in youth with higher BMI [7]. In the current study, uncontrolled eating or emotional eating was also positively correlated with energy leftover at dinner.…”
Section: Discussionsupporting
confidence: 60%
“…Previous studies have reported associations between different disturbed eating behaviours and obesity or risk of obesity . We observed associations between overeating and rapid eating (uncontrolled eating) and the degree of obesity at enrolment, while meal skipping and emotional eating was not associated with the degree of obesity in this study.…”
Section: Discussionsupporting
confidence: 45%
“…Previous studies that have examined the three domains of disturbed eating behaviour: cognitive restraint, emotional eating and uncontrolled eating, have focused more on the association between disturbed eating behaviour and body weight than on absolute prevalence . The several studies that have reported the prevalence of disturbed eating behaviours in children and adolescents with overweight or obesity have often concentrated on the domain of uncontrolled eating.…”
Section: Discussionmentioning
confidence: 99%
“…Snoek et al (9) and Martin-Garcia et al (19) . Evidence also supports a stronger association between adverse weight regulation and dietary restraint in girls compared to boys (22) .…”
Section: Ctfeqr17 and Anthropometric Measuresmentioning
confidence: 99%